1983
DOI: 10.1677/joe.0.0980241
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum concentration of luteinizing hormone in the female rat approaching puberty

Abstract: Concentrations of LH in the serum were estimated in rats bled either once or twice during a 15-day period preceding first ovulation. In rats bled once (between 09.00 and 17.00 h) serum concentrations showed little change between 15 and 9 days before first ovulation and averaged 16 micrograms/l (days -15 to -9). A shift in LH level, to a mean of 31 micrograms/l, was seen on day -8, whereafter LH concentrations increased gradually. Basal LH values of less than 10 micrograms/l were only found until day -4. The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
16
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 0 publications
5
16
0
Order By: Relevance
“…A similar period of high LH secretion around birth has been observed in calves (Challis et al, 1974), guinea-pigs (Donovan et al, 1975), humans (Kaplan and Grumbach, 1976) and rabbits (Berger et al, 1982 (Diekman et al, 1983) or at about 240 days (Camous el al, 1985). In agreement with our previous results in Large White gilts (Camous el al, 1985), (Boyar et al, 1974;Parker et al, 1975), in rats (Meijs-Roelofs et al, 1983;Urbanski and Ojeda, 1985) and in sheep (Foster et al, 1975;Foster and Ryan, 1981 (Rayford et al, 1974;Diekman et al, 1983;Camous et al, 1985) and in other species, such as sheep (Foster et al, 1975), rats (Dehler and Wuttke, 1975) and cattle (Schams et al, 1981). No significant variations in the concentration of plasma FSH were observed during the last weeks preceding puberty in agreement with Diekman et al (1983).…”
Section: Corticosteroid Concentrationssupporting
confidence: 91%
“…A similar period of high LH secretion around birth has been observed in calves (Challis et al, 1974), guinea-pigs (Donovan et al, 1975), humans (Kaplan and Grumbach, 1976) and rabbits (Berger et al, 1982 (Diekman et al, 1983) or at about 240 days (Camous el al, 1985). In agreement with our previous results in Large White gilts (Camous el al, 1985), (Boyar et al, 1974;Parker et al, 1975), in rats (Meijs-Roelofs et al, 1983;Urbanski and Ojeda, 1985) and in sheep (Foster et al, 1975;Foster and Ryan, 1981 (Rayford et al, 1974;Diekman et al, 1983;Camous et al, 1985) and in other species, such as sheep (Foster et al, 1975), rats (Dehler and Wuttke, 1975) and cattle (Schams et al, 1981). No significant variations in the concentration of plasma FSH were observed during the last weeks preceding puberty in agreement with Diekman et al (1983).…”
Section: Corticosteroid Concentrationssupporting
confidence: 91%
“…We were unable to detect a diurnal difference in basal LH levels, a result which appears to con flict with the results of Meijs-Roelofs et al (12]. Note, how ever, that our groups were very small compared with the hundreds of rats used by Meijs-Roelofs et al [12], We have, however, repeated and extended the observations of Blank and Mann [3] and have determined that this diurnal varia tion first appears between 23 and 26 days after birth, i.e., approximately 10 days before first ovulation in our colony. We have also shown that the minimal response to NAL is reflected in a similar change in the mediobasal hypotha lamic complement of opiate receptors.…”
Section: Discussionsupporting
confidence: 64%
“…This evidence, that as puberty approaches there may be a diurnal variation in the tonic opiate inhibition of gona dotrophin release, is supported by the findings of other in vestigators. Meijs-Roelofs et al [12] have found that from 5Received: April 14, 1986 Accepted after revision: July 30, 1986 days before the first ovulation, afternoon LH values were higher than in the morning. Urbanski and Ojeda [18] have also reported the development of a prepubertal increase in the amplitude of LH pulses in the afternoon, as well as the existence of an LH 'minisurge'.…”
mentioning
confidence: 99%
“…During the juvenileperipubertal transition period, the pulsatile pattern of lutein izing hormone (LH) changes to a greater afternoon amplitude compared to the morning [1,2], This alteration in LH pulse amplitude indicates a change at the hypothalamic level since this has been shown to be a gonadal independent event [3]. Whether or not this activation of the LH-releasing hormone (LHRH) releasing system to a low morning-high afternoon pulsatile secretory mode is the result of the removal of an inhibi tory tone or the development of excitatory inputs governing LHRH release has yet to be clearly defined [2,3). However, recent studies in rodents and primates have implicated exci tatory amino acids acting via N-methyl-Z>-aspartate receptors as being physiologically involved in the initiation of puberty [4,5].…”
mentioning
confidence: 99%